Mechanisms of action of plant growth promoting bacteria - Olanrewaju, Oluwaseyi Samuel; Glick, Bernard R.; Babalola, Olubukola Oluranti (World journal of microbiology & biotechnology, 2017)
The idea of eliminating the use of fertilizers which are sometimes environmentally unsafe is slowly becoming a reality because of the emergence of microorganisms that can serve the same purpose or even do better. Depletion of soil nutrients through leaching into the waterways and causing contamination are some of the negative effects of these chemical fertilizers that prompted the need for suitable alternatives. This brings us to the idea of using microbes that can be developed for use as biological fertilizers (biofertilizers). They are environmentally friendly as they are natural living organisms. They increase crop yield and production and, in addition, in developing countries, they are less expensive compared to chemical fertilizers. These biofertilizers are typically called plant growth-promoting bacteria (PGPB). In addition to PGPB, some fungi have also been demonstrated to promote plant growth. Apart from improving crop yields, some biofertilizers also control various plant pathogens. The objective of worldwide sustainable agriculture is much more likely to be achieved through the widespread use of biofertilizers rather than chemically synthesized fertilizers. However, to realize this objective it is essential that the many mechanisms employed by PGPB first be thoroughly understood thereby allowing workers to fully harness the potentials of these microbes. The present state of our knowledge regarding the fundamental mechanisms employed by PGPB is discussed herein.